The Compability Level of Tuberculin Skin Test and T-SPOT.TB, Sensitivity and Spesifisity of T-SPOT.TB in Detecting Latent Tuberculosis in Hemodialysis Patients - Astuti Setyawati; Reviono Reviono; Wachid Putranto (Jurnal Respirologi Indonesia, 2021)
Background: Controling Latent Tuberculosis Infection (LTBI) is important for the End TB Strategy program. The prevalence of LTBI and reactivation to active tuberculosis are increased in immunodeficiency conditions, such on hemodialialysis patients. Laten tuberculosis can be diagnosted by Tuberculin Skin Test (TST) and immunoglobulin release assay (IGRA). This diagnostic study aimed to determine the agreement level of TST and T-SPOT.TB, accurancy of T-SPOT.TB, and the correlation between T cluster of differentiation 4 (CD4+) cell counts with TST and T-SPOT.TB. Methods: This is a cross sectional study design was performed in hemodialysis patients of Dr. Moewardi Surakarta Hospital in May 2018. The study subject had TST and T-SPOT.TB examinations by using 2 Tuberkulin Unit (TU) of intradermal purified protein derivate (PPD) RT 23 (Biofarma, Bandung) and venous blood ELISPOT analysis, respectively. Statistical analysis used windows SPSS 21. Results: There were 30 study subjects. The prevalence of LTBI was 23.3%. The agreement level of TST and T-SPOT.TB was substantial (K=0.667;P<0.001). The sensitivity and specificity of T-SPOT.TB were 66.7% and 95.8%, respectively. There were no significant correlation of CD4+ T cell counts with TST (R=0,253;P=0,177), T-SPOT.TB ESAT-6SFUs (R=-0.169;P=0.317), T-SPOT.TB CFP-10 SFUs (R=0.006;P=0.975), and the highest value of T-SPOT.TB ESAT-6/CFP-10 SFUs, (R=-0.070;P=0.741). Conclusion: The prevalence of LTBI is high in hemodialysis patients, thus early detection is necessary. TST examination is recommended for LTBI diagnostic tool in hemodialysis patients because of its practical use, inexpensive, and does not require skilled personnel.